2017
DOI: 10.1093/aob/mcw260
|View full text |Cite
|
Sign up to set email alerts
|

Plant-parasitic nematodes: towards understanding molecular players in stress responses

Abstract: Background Plant–parasitic nematode interactions occur within a vast molecular plant immunity network. Following initial contact with the host plant roots, plant-parasitic nematodes (PPNs) activate basal immune responses. Defence priming involves the release in the apoplast of toxic molecules derived from reactive species or secondary metabolism. In turn, PPNs must overcome the poisonous and stressful environment at the plant–nematode interface. The ability of PPNs to escape this first line of plant immunity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 199 publications
(317 reference statements)
1
53
0
3
Order By: Relevance
“…Plant nematodes are obligate soilborne pathogens that infect plant roots. They have evolved sophisticated mechanisms for parasitism, with different feeding stylets and effector secretion for host manipulation [115,116]. They can be roughly divided into three main categories, according to the symptoms induced in their hosts: i) Cyst nematodes are associated with the sedentary genera Heterodera and Globodera; ii) root-knots are mostly caused by the sedentary species of Meloidogyne genus; and iii) lesions are mainly associated with the migratory endoparasitic genus Pratylenchus [117].…”
Section: Biotrophic Elegancementioning
confidence: 99%
“…Plant nematodes are obligate soilborne pathogens that infect plant roots. They have evolved sophisticated mechanisms for parasitism, with different feeding stylets and effector secretion for host manipulation [115,116]. They can be roughly divided into three main categories, according to the symptoms induced in their hosts: i) Cyst nematodes are associated with the sedentary genera Heterodera and Globodera; ii) root-knots are mostly caused by the sedentary species of Meloidogyne genus; and iii) lesions are mainly associated with the migratory endoparasitic genus Pratylenchus [117].…”
Section: Biotrophic Elegancementioning
confidence: 99%
“…Genome and transcriptome studies from PPNs have revealed genes orthologous to Daf-16 and Skn-1 from C. elegans in the Meloidogyne, Pratylenchus, and Bursaphelenchus genera 39,[58][59][60] . The high level of sequence conservation suggests similar functions to those observed in C. elegans 13,35,59 . Studies of comparative genomes in PPNs have identified numerous defense genes from the DAF-16 and SKN-1 networks involved in ROS scavenging, coding proteins linked to the antioxidant pathway, superoxide dismutases (SOD), catalases (CAT), glutathione S-transferases (GST), glutathione peroxidase (GPX), and peroxiredoxins (PRDX) 11,18,20,58,61 .…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, the 14-3-3 scaffolding proteins bind to the phosphorylation sites of DAF-16 and contribute to its sequestration within the cytoplasm 51,52 . In the nucleus, the DAF-16 and SKN-1 TFs are responsible for the transcriptional activation of up to 500 and 846 genes, respectively 13,53 . These activated genes belong to several functional groups and are implicated in the aging and longevity process and the antioxidant, detoxification, and protein unfolding response pathways [54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations